2018
DOI: 10.1167/iovs.18-24751
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Pterygium Cells by Antagonists of Growth Hormone–Releasing Hormone Receptors

Abstract: The aim of the study was to investigate the signaling of growth hormone-releasing hormone receptor (GHRH-R) in the pathogenesis of pterygium and determine the apoptotic effect of GHRH-R antagonist on pterygium epithelial cells (PECs). METHODS. Fourteen samples of primary pterygium of grade T3 with size of corneal invasion ‡ 4 mm were obtained for investigation by histology, immunofluorescence, electron microscopy, explant culture, and flow cytometry. RESULTS. We found that PECs were localized in the basal laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Downregulated pathways also provide us with pieces of evidence of disease progression. Hormone-related pathways are significantly downregulated; some research reported that hormone-related growth factors and receptors are implicated in pterygium ( 45 , 46 ). Even though some hormones can affect corneal morphology, physiology, and metabolism, there is few of evidence indicating that hormones directly participate in the development of pterygium ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated pathways also provide us with pieces of evidence of disease progression. Hormone-related pathways are significantly downregulated; some research reported that hormone-related growth factors and receptors are implicated in pterygium ( 45 , 46 ). Even though some hormones can affect corneal morphology, physiology, and metabolism, there is few of evidence indicating that hormones directly participate in the development of pterygium ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium is a fibrovascular neoformation composed of epithelium and highly vascular loose subepithelial connective tissue (20). Previous studies have demonstrated that apoptotic and oncogenic proteins, microsatellite instability, inflammatory mediators, extracellular matrix modulators, EMT and other factors are involved in the development of pterygium (4,(9)(10)(11)13). However, to the best of our knowledge, the precise molecular mechanisms of pterygium pathogenesis have not been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium exhibits tumor-like features, including propensity to invade normal tissue, recurrence after excision and coexistence with premalignant lesions (4,7,8). Previous studies have demonstrated that pterygium epithelial cells (PECs) are highly proliferative, have features of epithelial-mesenchymal transition (EMT) and overexpress anti-apoptotic proteins (9)(10)(11)(12)(13). Livin is a member of the inhibitors of apoptosis protein (IAP) family (14), which function in tumor initiation, progression and resistance to chemotherapy (15).…”
Section: Introductionmentioning
confidence: 99%
“…After organ culturing, selected lenses were sectioned for hematoxylin and eosin (H&E, C0105S, Beyotime) staining and urate deposition staining with Gomori methenamine silver (GMS, BB-44715, Bestbio, Shanghai, China), as we previously reported [ 11 , 46 ]. The lenses were fixed in 4% paraformaldehyde, dehydrated, embedded in paraffin, and sectioned coronally at 5 μm thickness.…”
Section: Methodsmentioning
confidence: 99%